การพัฒนาแบบจำลองการสั่นสะเทือนเนื่องจากการระเบิด : รายงานฉบับสมบูรณ์ - สง่า ตั้งชวาล (จุฬาลงกรณ์มหาวิทยาลัย, 1995)
Vibration from detonated wave pulse which is shock wave was reviewed in order to develop models for transient vibration. Selected systems were Single Degree of Freedom System and Multidegree of Freedom System. Numerical analyses were derived to find the optimum solution of shock wave that represents as response spectrum. Modeling programs were written for both SDF and N-DOF systems. It is in form of package program bu suing C++ language and runs under Microsoft Windows version 3.1 Thau Edition